2021
DOI: 10.1016/j.jiac.2021.02.029
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a newly developed antigen test (QuickNavi™-COVID19 Ag) for SARS-CoV-2: A prospective observational study in Japan

Abstract: Introduction: Several antigen tests for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been developed worldwide, but their clinical utility has not been well established. In this study, we evaluated the analytical and clinical performance of QuickNavi™-COVID19 Ag, a newly developed antigen test in Japan. Methods: This prospective observational study was conducted at a PCR center between October 7 and December 5, 2020. The included patients were referred from a local public health center and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 14 publications
4
55
1
Order By: Relevance
“…On the other hand, the QuickNavi-COVID19 Ag test provided 100% specificity in both the present study and our previous study 3 . Although it is necessary to verify whether similar results can be obtained in other settings, false positives should be avoided to prevent unnecessary additional testing and inappropriate isolation measures 15 .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…On the other hand, the QuickNavi-COVID19 Ag test provided 100% specificity in both the present study and our previous study 3 . Although it is necessary to verify whether similar results can be obtained in other settings, false positives should be avoided to prevent unnecessary additional testing and inappropriate isolation measures 15 .…”
Section: Discussionsupporting
confidence: 68%
“…Although paired comparison between different swab samples lacked in this study, our study demonstrated that anterior nasal samples provided a lower antigen test sensitivity than our previous study evaluating nasopharyngeal samples 3 . Nevertheless, this lower sensitivity of 72.5% may be acceptable since according to the reported systematic review, sensitivity of nasal swab was 86% in comparison to nasopharyngeal swab by RT-PCR 9 .…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In the model false positive tests are ignored, reflecting high specificity. While originally only PCR tests had such quality, antigen tests have been substantially improved [45][46][47][48][49][50]. While PCR tests need to be processed in a lab, their antigen-based counterparts are available as rapid tests that return the test result after 5-20 minutes.…”
Section: Antigen Testsmentioning
confidence: 99%